The Use of Botulinum Toxin in Medicine: Safety and Efficacy Based on the Latest Research - Anna Jaremek; Joanna Kępa; Norbert Kandefer; Michał Wyszkowski; Aleksandra Grabarczyk; Anna Pawlak; Sylwia Grad; Małgorzata Gregorek; Paweł Gregorek (Kazimierz Wielki University, 2023)
Introduction and aim of the study: Botulinum toxin, produced by anaerobic bacteria of the Clostridium botulinum family, is one of the most potent organic compounds known to man. Despite its toxicity, it has found widespread use in medicine. From applications in aesthetic medicine, through the treatment of various disease entities, botulinum toxin has become an extremely valuable tool in the hands of doctors. The aim of this study is to review the latest research on the use of botulinum in medicine, with an emphasis on its safety and effectiveness.   Methodology: The review work is mainly based on articles searched in the Pubmed and Google Scholar databases in the years 2016-2023. The study was conducted by reviewing keywords such as "botulin", "botulin toxin", "botulin treatment", "botulin aesthetic". Current state of knowledge: Botulinum is used in the treatment of such disease entities as hyperhidrosis, cervical dystonia, migraines, neurogenic bladder, as well as in the treatment of scars and wrinkles. The use of botulinum in medicine is safe, provided that it is used by qualified specialists and in appropriate doses. An area that requires further research is the impact of long-term botulinum therapy on the antibodies produced against the toxin. Additionally, an important area for further research is patient monitoring, appropriate dose adjustment and frequency of administration, which in turn can increase the effectiveness of treatment. Summary: Botulinum toxin is an effective tool in medicine, which has many applications. However, as with any drug, it requires appropriate use and understanding of potential side effects. Further research and education are key to fully exploiting its potential and assessing the risk associated with long-term use.